Meaning does not have to be rendered in words: Intersemiotic translation in digital religious infographics - Mowafy, Mai (Indonesian Journal of Applied Linguistics, 2024)
Data visualization is becoming widespread nowadays as people grasp images faster than verbal information. Infographics delineate information visually to be easily intelligible to the audience. They are creative discursive spaces where complex information can be disseminated in a variety of contexts. Religious Infographics discourse presents a fertile area of research that is not fully explored in academia. Coined by Jakobson (1959), “intersemiotic translation” refers to the interpretation of linguistic signs through non-verbal resources. This paper applies a qualitative descriptive approach to analyze fifteen religious infographics designed by Yaqeen institution for Islamic research. It applies Lim’s (2004) Integrative Multi-semiotic Model (IMM), which encompasses three planes: the expression plane, the content plane, and the context plane, to show how meanings are constructed in digital religious infographics. This study highlights the strategies used in religious infographics to resemiotize original meanings on the three planes. The findings of this paper show that intersemiotic translation is used in digital religious infographics to represent meanings and discuss important topics regarding faith, politics and theology, psychology and mental health, history, family, and community. The study invites further investigation of religious infographics in a more diversified corpus.